Behavior Management Training for Newly Graduated Teachers: A Randomized-Controlled Trial - McGuire, Stacy N.; Meadan, Hedda; Xia, Yan (Behavioral disorders, 2023)
Students who engage in challenging behavior should receive preventive and intervening supports and services in general education settings based on their individual needs. These supports are necessary for students to be successful in school, yet preservice teachers receive limited education and training in both classroom and behavior management. As such, the purposes of this study were to identify the effects of an online behavior management training on newly graduated elementary education teachers immediately after completing their teacher preparation programs and to explore their perceptions regarding the training. A randomized-controlled trial was used, with 39 participants in the intervention group and 44 participants in the waitlist-control group. Results indicated participants in the intervention group showed a statistically significant increase in both knowledge and self-efficacy compared with participants in the waitlist-control group, and insignificant gains in their ability to analyze the use of behavior management strategies. Participants reported feeling the training was highly effective and were eager to implement the strategies with their future students.